Exploring the Impact of Augmented Reality on Meaningful Learning in Islamic Religious Education: A Quantitative Analysis - Ulul Albab; Ahmad Ta’rifin; Dirasti Novianti; Hani Hasnah Safitri (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2025)
This study aims to investigate the effect of Augmented Reality (AR) on the meaningfulness of learning Islamic religious education. AR tested in this study include Smart Glasses AR (X1), Mobile Augmented Reality Application (X2), and AR in Books (X1). While the learning meaningfulness variable is divided into three indicators by referring to Clark and Daryanes' theory including problem solving (Y1), critical thinking skills (Y2), and learning motivation (Y3). This quantitative research uses multiple linear regression analysis model. Data was collected through a survey of 99 research respondents. The results show that AR has the most significant impact in increasing learning motivation, as its additional elements create an engaging and interactive learning experience. AR's influence on critical thinking ability ranked second, as the technology encourages the development of analytical and evaluative skills. This is due to AR's focus on improving concept understanding and learner engagement in the learning process. In contrast, the least impact of AR was seen on problem-solving ability, where this technology is more likely to increase motivation and concept understanding rather than providing direct solutions to problems. These findings contribute to improving the understanding of how AR can shape more meaningful learning experiences in the context of Islamic religious education.